Estratificação de risco para predição de fibrilação atrial no pós-operatório de cirurgias cardíacas - Araújo Neto, João Lins de (2022)
Introduction: Postoperative atrial fibrillation (POAF) is the most common sustained arrhythmia after cardiac surgery, occurring in approximately 30% of operated patients. The occurrence of the arrhythmia is associated with an increased risk of stroke, increased length of hospital stay and death. In a context of strong evidence in the scientific literature recommending prophylactic treatment for POAF, and the precariousness of data indicating which patients should receive such treatment, the present study aimed to develop a new predictive score for atrial fibrillation in the postoperative period of cardiac surgeries. Methods: A retrospective cohort study was carried out with a non-probabilistic sample consisting of 989 patients. Adult patients who underwent cardiac surgery, except for heart transplantation and implantation of a ventricular assist device, participated in the study. Patients with previous atrial fibrillation or those using amiodarone were excluded. The analyzed variables were submitted to univariate analysis regarding the occurrence of POAF, and then to multivariate analysis using logistic regression. Accuracy and specificity were calculated, as well as model calibration and discrimination. Results: The variables that were statistically significant in the multivariate analysis were: age greater than or equal to 60 years (p<0.001), left atrial enlargement on echocardiogram (p=0.025), use of inotropes in the first 24 hours after surgery (p =0.002) and need for reoperation in the first 24 hours (p=0.016). To compose the score, each of these four variables was assigned a point. An accuracy of 77% and a specificity of 99% were obtained for predicting the outcome in the proposed score, and it was observed that a score greater than or equal to three is related to a risk of 34% (95%CI: 27,8 to 39,6%) occurrence of FAPO. Conclusion: The score proposed in this study, consisting of the variables age greater than or equal to 60 years, left atrial enlargement on echocardiography, use of inotropes in the first 24 hours after surgery and need for reoperation in the first 24 hours, showed an accuracy of 77% in predicting the occurrence of POAF.